Impact of the COVID-19 crisis on work and private life, mental well-being and self-rated health in German and Swiss employees: a cross-sectional online survey - Martin Tušl; Rebecca Brauchli; Philipp Kerksieck; Georg Friedrich Bauer (BMC, 2021)
Abstract Background The COVID-19 crisis has radically changed the way people live and work. While most studies have focused on prevailing negative consequences, potential positive shifts in everyday life have received less attention. Thus, we examined the actual and perceived overall impact of the COVID-19 crisis on work and private life, and the consequences for mental well-being (MWB), and self-rated health (SRH) in German and Swiss employees. Methods Cross-sectional data were collected via an online questionnaire from 2118 German and Swiss employees recruited through an online panel service (18-65 years, working at least 20 h/week, various occupations). The sample provides a good representation of the working population in both countries. Using logistic regression, we analyzed how sociodemographic factors and self-reported changes in work and private life routines were associated with participants' perceived overall impact of the COVID-19 crisis on work and private life. Moreover, we explored how the perceived impact and self-reported changes were associated with MWB and SRH. Results About 30% of employees reported that their work and private life had worsened, whereas about 10% reported improvements in work and 13% in private life. Mandatory short-time work was strongly associated with perceived negative impact on work life, while work from home, particularly if experienced for the first time, was strongly associated with a perceived positive impact on work life. Concerning private life, younger age, living alone, reduction in leisure time, and changes in quantity of caring duties were strongly associated with perceived negative impact. In contrast, living with a partner or family, short-time work, and increases in leisure time and caring duties were associated with perceived positive impact on private life. Perceived negative impact of the crisis on work and private life and mandatory short-time work were associated with lower MWB and SRH. Moreover, perceived positive impact on private life and an increase in leisure time were associated with higher MWB. Conclusion The results of this study show the differential impact of the COVID-19 crisis on people's work and private life as well as the consequences for MWB and SRH. This may inform target groups and situation-specific interventions to ameliorate the crisis.